Manifestation of epilepsy in a patient with EED-related overgrowth (Cohen-Gibson syndrome) - Hetzelt, Katalin; Winterholler, Martin; Kerling, Frank; Rauch, Christophe; Ekici, Arif Bülent; Winterpacht, Andreas; Vasileiou, Georgia; Uebe, Steffen; Thiel, Christian; Kraus, Cornelia; Reis, André; Zweier, Christiane (American Journal of Medical Genetics Part A, 2021)
Cohen-Gibson syndrome is a rare genetic disorder, characterized by fetal or early childhood overgrowth and mild to severe intellectual disability. It is caused by heterozygous aberrations in EED, which encodes an evolutionary conserved polycomb group (PcG) protein that forms the polycomb repressive complex-2 (PRC2) together with EZH2, SUZ12, and RBBP7/4. In total, 11 affected individuals with heterozygous pathogenic variants in EED were reported, so far. All variants affect a few key residues within the EED WD40 repeat domain. By trio exome sequencing, we identified the heterozygous missense variant c.581A > G, p.(Asn194Ser) in exon 6 of the EED-gene in an individual with moderate intellectual disability, overgrowth, and epilepsy. The same pathogenic variant was detected in 2 of the 11 previously reported cases. Epilepsy, however, was only diagnosed in one other individual with Cohen-Gibson syndrome before. Our findings further confirm that the WD40 repeat domain represents a mutational hotspot; they also expand the clinical spectrum of Cohen-Gibson syndrome and highlight the clinical variability even in individuals with the same pathogenic variant. Furthermore, they indicate a possible association between Cohen-Gibson syndrome and epilepsy.
CRIS-Team WoS Importer:2021-09-24